2020
DOI: 10.4103/ijcm.ijcm_436_19
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quality of life of primary caregivers of Egyptian asthmatic children and adolescents

Abstract: Background: Asthma as a serious public health problem worldwide exerts a serious load on children's health-related quality of life (HRQOL) and their families. Objective: We assess the HRQOL of the primary caregivers of Egyptian asthmatic children and adolescents and its relation to HRQOL of their children and asthma severity. Materials and Methods: A cross-sectional study was conducted on 128 pairs of asthmatic children (7–16 years) and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…According to government data, it is estimated that 12.5% of Colombians have asthma, while it is reported that prevalence of asthma in Colombian children ranges between 8% and 10.4% 4,5 . Data reveal that more than half of patients have inadequate therapeutic adherence to inhaled treatments, which leads to inadequate asthma control and a poor quality of life (QoL) for them and for their caregivers 1,2,6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to government data, it is estimated that 12.5% of Colombians have asthma, while it is reported that prevalence of asthma in Colombian children ranges between 8% and 10.4% 4,5 . Data reveal that more than half of patients have inadequate therapeutic adherence to inhaled treatments, which leads to inadequate asthma control and a poor quality of life (QoL) for them and for their caregivers 1,2,6 …”
Section: Introductionmentioning
confidence: 99%
“…4,5 Data reveal that more than half of patients have inadequate therapeutic adherence to inhaled treatments, which leads to inadequate asthma control and a poor quality of life (QoL) for them and for their caregivers. 1,2,6 There are many factors associated with inadequate therapeutic adherence to asthma maintenance therapy that have been well documented in the literature. 1,7 Therapeutic adherence is not only affected by conditions related to the disease, such as duration and severity, but also depend on treatment-related characteristics such as frequency of dosing and side effects, socioeconomic factors, the physician-patient relationship, and adequate health system access.…”
mentioning
confidence: 99%